Regulating human embryonic research in Malaysia: a proposal for a model legislation / Dr. Fadilah Abd Rahman, Prof. Dr. Puteri Nemie Jahn Kassim and Prof. Madya Dr. Nasimah Husin - Abd Rahman, Fadilah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Today, human embryos created under IVF programs have tremendously become one of the important subjects of research and experimentations in many countries. The research is regarded as very important in developing solutions for the treatment and prevention of infertility and other diseases or disorders in human. In Malaysia and many other countries, embryonic research has taken place through professional self-regulation in the absence of comprehensive legislation. Given the fact that IVF human embryos are entity of human origin that must be protected from abuse and frivolous uses, embryonic research must be regulated by statutory legislation. This model legislation is developed to fulfil the absence of a statutory legislation to govern matters involving research using human embryos created outside the human body. It is designed as a result of harmonization between Shariah Law and The Human Fertilization and Embryology Act of 1990 of the United Kingdom. This model is very unique in itself as it is developed after thorough study on the position of embryonic research from the shariah point of view, blended with the provisions of HFE Act 1990 UK and the vast experiences that it has since 1984 and further adapted with local culture and values. Valuable inputs and recommendations made by major outstanding local scientists and fertility specialists in regulating embryonic research is another unique part of the model legislation. Given the fact that research involving IVF human embryos has already taken place in Malaysia, this model of legislation would serve as a basis in regulating embryonic research in Malaysia and beyond, via statutory legislation.